Bereavement Support for Siblings after Neonatal Loss: an Online Survey of U.S. Training Centers - Tillhof, Katie; Krawzak, Katie; Batza, Jennifer; Feltman, Dalia M. (American Journal of Perinatology, 2022)
Objective The aim of this study was to examine bereavement support for siblings of patients who die in the neonatal intensive care unit (NICU) given the adverse effects of unprocessed grief and the paucity of information on children whose newborn siblings dieStudy Design This was an anonymous online original survey assessing pre-COVID-19 pandemic bereavement services for NICU families, clinicians' attitudes toward support interventions, challenges, and center characteristics. In spring 2020, nurse managers at 81 U.S. centers with neonatology and maternal–fetal medicine fellowship programs were asked to identify the individual most knowledgeable in their NICU's bereavement support services; these individuals were invited by email to complete an original online survey. Chi testing and odds ratios (ORs) compared responses from centers reporting involvement of palliative care teams (PCT) in NICU sibling bereavement versus no PCT.Results Fifty-six percent (45 of 80) of invitees responded. Most (77%) NICUs permitted perimortem sibling visitation. Challenges included sparse community resources and limited direct sibling contact. Sixty-nine percent (n = 31) of centers were grouped as PCT. PCT respondents reported eightfold higher chances of providing direct education to the sibling (OR, 7.7; 95% confidence interval, 1.7–34; p = 0.01). Views on appropriateness of sharing educational information with extended family, babysitters, and teachers did not differ. While notifying pediatricians of families experiencing NICU death was more common in PCT (p = 0.02), most respondents reported having “no individual responsible for such communications" (52% PCT vs. 100%, p = 0.001).Conclusion Despite limited direct contact with siblings of NICU patients who die, efforts are made to involve them in bereavement activities. Opportunities to support these children were identified. Where available, palliative care teams can help provide bereaved siblings with direct education. We recommend formalizing communication mechanisms to ensure that if a NICU patient dies and has surviving siblings, the outpatient physicians caring for these siblings are informed.Key Points
Keywords: bereavement; palliative care; newborn; NICU; perinatal death